Pembinaan Laundry Di Perumahan Cipta Asri Kota Batam Dalam Membangun Strategi Penetapan Harga Untuk Meningkatkan Pendapatan Usaha - Dian Lestari Siregar (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2019)
Many MSMEs failed in the initial process of operation, one of the reasons for the failure of these MSMEs was a lack of analysis of pricing strategies. Batam as an industrial city and one of the main destinations for productive age residents to find work. The dense population and working hours from morning to morning again make people not have enough time to take care of their homework. So the existence of laundry business is one solution to overcome these problems. The number of laundry businesses in Batam certainly narrows competition. So every business must have new innovations, new ideas and knowledge in managing businesses to pricing strategies. When the business management is good and the entrepreneur has the knowledge of arranging pricing, the entrepreneur will certainly be able to know for sure the benefits that are earned each month. The purpose of this service activity is to provide guidance on business management, pricing strategies. The methods used are interviews, providing guidance, and business consulting. The results of this activity are laundry businesses in Cipta Asri, Batam City, which have good business management, understand the pricing strategy and are able to calculate business profits every month.